2019
DOI: 10.1021/acsami.9b09722
|View full text |Cite
|
Sign up to set email alerts
|

Bendable Network Built with Ultralong Silica Nanowires as a Stable Separator for High-Safety and High-Power Lithium-Metal Batteries

Abstract: Separators are key safety components for electrochemical energy storage systems. However, the intrinsic poor wettability with electrolyte and low thermal stability of commercial polyolefin separators cannot meet the requirements of the ever-expanding market for high-power, high-energy, and high-safety power systems, such as lithium-metal, lithium-sulfur, and lithium-ion batteries. In this study, scalable bendable networks built with ultralong silica nanowires (SNs) are developed as stable separators for both h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 43 publications
(55 reference statements)
1
23
0
Order By: Relevance
“…Recently, intensive investigations on separator modification have been realized and applied in Li‐metal protection. [ 51,163–176 ] An advanced separator with high mechanical strength can prevent Li dendrites from penetrating it. In addition, the narrow pore size distribution and functionalities of modified separators can regulate homogenous Li‐ion flux near the electrode surface and thus promote uniform Li nucleation and growth.…”
Section: Porous Separatorsmentioning
confidence: 99%
“…Recently, intensive investigations on separator modification have been realized and applied in Li‐metal protection. [ 51,163–176 ] An advanced separator with high mechanical strength can prevent Li dendrites from penetrating it. In addition, the narrow pore size distribution and functionalities of modified separators can regulate homogenous Li‐ion flux near the electrode surface and thus promote uniform Li nucleation and growth.…”
Section: Porous Separatorsmentioning
confidence: 99%
“…As compared with results across the published reports, the devices with the BNNTMs separator exhibit excellent Li dendritesuppressing ability to enable exceptional small overpotential ( Supplementary Fig. 13) and cycling stability with a cumulative lifetime capacity exceeding 4,000 mAh cm -2 , exceeding the lifetime capacity of typical LIBs (typically < 2,000 mAh cm -2 ) 44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60 (Fig. 4j) (Details are shown in Supplementary Table S3).…”
Section: Lithium-ion Transference Number (T LImentioning
confidence: 72%
“…[107][108][109] In addition to HAP NWs, Al 2 O 3 and SiO 2 NWs with high thermal stability and good electrochemical stability were also investigated for constructing high-safety LIB separators. [92,110,111] For example, He et al developed a pure inorganic separator for LIBs based on Al 2 O 3 NWs. [110] The Al 2 O 3 NWs separator was flexible and with a pore size around 100 nm.…”
Section: Fire-resistant Separators and Electrodesmentioning
confidence: 99%
“…In another work, a bendable porous separator made from ultralong SiO 2 NWs was prepared for LIBs. [111] Thermogravimetry analysis (TGA) results showed that the SiO 2 NWs separator showed no weight loss up to 700 °C. Moreover, the highly porous nature (≈73% in porosity) and polar surface enabled the inorganic separator with excellent Reproduced with permission.…”
Section: Fire-resistant Separators and Electrodesmentioning
confidence: 99%